Pendampingan Kelompok Tani Anugrah Memanfaatkan Eceng Gondok Sebagai Bahan Baku Pakan Ikan Gurame - Saronom Silaban; Murniaty Simorangkir; Juniastel Rajagukguk (Universitas Prof. Dr. Hazairin, SH, 2021)
Assistance to Anugrah Farmers Group Utilizing Water Hyacinth as a Raw Material for Carp Feed Water hyacinth (Eichornia crassipes) is not only harmful but also beneficial because it can be used as animal fodder, fish fodder, organic fertilizer, and biogas production and water purification. Water hyacinth like other plants contains protein needed by carp (Osphronemus gouramy Lac). The purpose of this community service activity is to provide assistance to partners in utilizing water hyacinth as a raw material for carp feed. The approach taken is the methods namely planning, training and mentoring. The results of the community service activity show that partners already have knowledge in processing water hyacinth as a raw material for fish feed, which can reduce high production costs. Comparison of the price of commercial animal feed and animal feed made from water hyacinth is 12,000 IDR compared to 6,058 IDR and can accelerate the growth of carp.